ANIMATION RESEARCH: CONSTRUCTING BANGSAWAN IN 2D FORMAT: KAJIAN ANIMASI: PEMBANGUNAN BANGSAWAN DALAM FORMAT 2D - Mohd. Nasir, Nur Yuhanis; Bujang, Rahmah (Jurnal Pengajian Melayu (JOMAS), 2013)
This paper presented is a Doctor of Philosophy degree research in progress by the first named presenter of the paper. The paper shares her experiences and efforts in constructing a 2D animation work of the Bangsawan theatre. The work process involves a good understanding of the Bangsawan live theatre phenomenon and to construct an original script taken from the Malay historical source of Hikayat Seri Kelantan. The major part however is the animation work process of the Bangsawan story set within the Bangsawan format of live theatre. To construct the 2D animation work, it is decided upon the choice of projecting the tale of a female Malay ruler, Puteri Saadong of Kelantan whose reign was during the end of the 18th century. Keywords: Bangsawan, 2D animation, digital technology, Hikayat Seri Kelantan, story construction. Artikel ini membincangkan kajian yang sedang dijalankan oleh penulis pertama dan berkongsi tatakerja yang terlibat dalam usaha mengkonstruk teater Bangsawan dalam bentuk persembahan animasi 2D. Bagi memastikan skrip yang ditulis menepati ciri-ciri drama Bangsawan sebenar, kajian ini menuntut pemahaman pengkaji terhadap fenomena Bangsawan. Skrip kajian ini dibuat berdasarkan sumber dari Hikayat Seri Kelantan. Bahagian penting dalam kajian ini adalah kerja pembangunan animasi yang memilih untuk menampilkan cerita Puteri Saadong; seorang pemerintah wanita dari Kelantan yang berakhir pada abad ke-18. Kata kunci: Bangsawan, animasi 2D, teknologi digital, Hikayat Seri Kelantan, pembinaan cerita.